Faculty Senate, Agenda, October 17, 2002 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2002)
Valdosta State University. Faculty Senate, Agenda, October 17, 2002.
1 electronic document. Faculty Senate, Agenda, October 17, 2002. 2 pages. 98,056 bytes.
Keywords: Valdosta State University. Faculty Senate; Committees; Electronic records; Corporation reports